The Aga Khan University Hospital in Karachi and the Unity of Din and Dunyā - Sara Honarmand Ebrahimi (ABE Journal)
In 1969, the Aga Khan IV, the forty-ninth hereditary Imam (spiritual and temporal leader) of the global Shiʻi Ismaili Muslim community, selected a “suitable team” to design and construct the Aga Khan University Hospital in Karachi, Pakistan. The buildings began going up in 1971, and the complex was completed in 1985. This article situates the design and planning of the University Hospital in the context of 20th-century hospital architecture to explore how it was designed and planned differently from Western models of the period. It shows that the University Hospital was designed to embody the Aga Khan IV’s theological quest for harmony between dīn (faith) and dunyā (world). Understanding and appreciating this theological quest helps going beyond merely adding the University Hospital to the historiography of hospital architecture in the 20th century to discern how it diversifies this historiography. Since the quest for harmony between dīn and dunyā raises the question of whether the Aga Khan IV supported ambitions for Pakistan as an Islamic state, the article also reflects, although briefly, on the place of the University Hospital in ambitions for Pakistan.